Effectiveness of Effleurage and Counter-Pressure Massages in Reducing Labor Pain - Santiasari, Retty Nirmala; Nurdiati, Detty Siti; Lismidiati, Wiwin; Saudah, Noer (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
labor. Effects of labor pain includes inflammation in uterus and labor dystocia. Effleurage and counter-pressure massage were complementary treatment to relieve pain. This study aimed to analyze effectiveness of effleurage and counter-pressure massages for reducing labor pain in stage 1 of active labor phase. This study used quasi experiment design with pre-post test non-equivalent control group. Research subjects were 68 mothers in stage 1 of active labor phase, which were divided evenly to two groups. Sampling collection technique used consecutive sampling. Independent variables were effleurage and counter-pressure, while dependent variables were decline of labor pain. Instrument to assess labor pain was Numeric Rating Scale (NRS). Data were analyzed using Wilcoxon and Mann Whitney. Labor pain before and after intervention in effleurage group were 9.26±1.05 and 6.88±1.22, respectively (p=0.00). Meanwhile, the respective numbers in counter-pressure groups were 9.00±0.98 and 6.59±1.28 (p=0.00). Average labor pain decline in effleurage and counter-pressure groups were 2.38 and 2.41, respectively (p=0.74). There was no significant difference between effleurage and counter-pressure in reducing labor pain. Keywords: Labor pain, Effleurage, Counter-pressure